Light controls gene functions through alternative splicing in fungi - Yifan Li; Huanhong Lu; Degang Guo; Xiaoyan Li; Fei Qi; Jian Zhang; Reinhard Fischer; Qirong Shen; Zhenzhong Yu (Proceedings of the National Academy of Sciences, 2025)
Light controls important biological processes in fungi by regulating transcriptional gene activation. Here, we found that beyond the regulation of mRNA transcript abundance, light regulates alternative splicing (AS) in the filamentous fungi Aspergillus nidulans , Trichoderma guizhouense, and Neurospora crassa . Blue light-regulated AS was involved in ergothioneine biosynthesis and conidiation in T. guizhouense , which required the blue light receptor BLR1. Blue light activated the MAPK HOG (Sak) pathway which then transmitted the signal via the serine/threonine kinase SRK1 to the AS key regulator SRP1. SRK1 and SRP1 are important for light-induced conidiation. The light-activated HOG pathway led to an increase of the SRK1 protein level and its phosphorylation status. Phosphorylated SRK1 translocated from the cytoplasm to the nucleus to interact with SRP1, thereby regulating AS efficiency. This study unravels another level of complexity of fungal environmental sensing and responses and also first describes the entire cascade from an environmental signal to the splicing machinery.